ICT ve strategickém řízení podniků - Nováková, Natália (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Predmetom diplomovej práce je navrhnutie využitia ICT pri implementácií business stratégie vo firme M&P optik s.r.o.. Práca skúma kľúčové interné a externé faktory súvisiace s implementáciou business stratégie firmy, hodnotí ich a navrhuje konkrétnu realizáciu nástrojov ICT pre podporu dosiahnutia strategických cieľov.

The subject of the diploma thesis is proposing the use of ICT in the implementation of a business strategy in the company M&P optik s.r.o.. The thesis examines key internal and external factors related to the implementation of the business strategy of the company, evaluates them, and proposes the specific implementation of ICT to achieve strategic objectives.
ICT in Strategic Management of Companies
Keywords: Stratégia; business stratégia; business model CANVAS; konkurenčná výhoda; ICT podpora business stratégie; Strategy; business strategy; business model CANVAS; competitive advantage; ICT support for business strategy